Three-Body Abrasion Corrosion Studies of High-Cr Cast Irons: Benefits and Limitations of Tribo-electrochemical Methods - Stachowiak, G.; Salasi, Mobin; Stachowiak, G. (2015)
High-Cr white cast irons (WCIs) are multiphase alloys commonly used in aqueous industrial environments in applications that require both high abrasion and high corrosion resistance. Various electrochemical techniques can be useful in elucidating tribocorrosion characteristics of metallic materials undergoing wear in a corrosive environment. This study is focused on the interpretation of electrochemical measurements applied to three-body abrasion corrosion contacts of high-Cr WCIs. Particular attention has been paid to determine whether tribo-electrochemical data can pick up any effects that the multiphase microstructure of WCIs may have on the tribocorrosion characteristics, especially in environments containing chloride ions. Since both wear and corrosion of multiphase alloys are usually not uniform, their tribocorrosion behaviour is difficult to study and is still poorly understood. The experimental results are discussed in terms of benefits and limitations of tribo-electrochemical techniques such as polarization (potentiostatic, potentiodynamic) and electrochemical noise (galvanic coupling, potentiostatic) in studying abrasion corrosion behaviour of high-Cr WCIs. The application of high-resolution surface analysis techniques (microprobe, NanoSIMS, C-AFM and SKPFM), used in support of the electrochemical data interpretation, is also demonstrated.